Monoclonal gammopathies of clinical significance (MGCS): In pursuit of optimal treatment - Oganesyan, Artem; Gregory, Andrew; Malard, Florent; Ghahramanyan, Nerses; Mohty, Mohamad; Kazandjian, Dickran; Mekinian, Arsène; Hakobyan, Yervand (Frontiers in Immunology, 2022)
Monoclonal gammopathy of clinical significance (MGCS) represents a new clinical entity referring to a myriad of pathological conditions associated with the monoclonal gammopathy of undetermined significance (MGUS). The establishment of MGCS expands our current understanding of the pathophysiology of a range of diseases, in which the M protein is often found. Aside from the kidney, the three main organ systems most affected by monoclonal gammopathy include the peripheral nervous system, skin, and eye. The optimal management of these MGUS-related conditions is not known yet due to the paucity of clinical data, the rarity of some syndromes, and limited awareness among healthcare professionals. Currently, two main treatment approaches exist. The first one resembles the now-established therapeutic strategy for monoclonal gammopathy of renal significance (MGRS), in which chemotherapy with anti-myeloma agents is used to target clonal lesion that is thought to be the culprit of the complex clinical presentation. The second approach includes various systemic immunomodulatory or immunosuppressive options, including intravenous immunoglobulins, corticosteroids, or biological agents. Although some conditions of the MGCS spectrum can be effectively managed with therapies aiming at the etiology or pathogenesis of the disease, evidence regarding other pathologies is severely limited to individual patient data from case reports or series. Future research should pursue filling the gap in knowledge and finding the optimal treatment for this novel clinical category.